ABA-GA antagonism and modular gene networks cooperatively drive acquisition of desiccation tolerance in perilla seeds - Yang, Xiaohuan; Chen, Minghao; Liu, Mingwang; Li, Bowen; Sun, Zhichao; Lu, Ailian; Zhang, Sen; Shi, Xinghai; Ren, Jun; Qin, Xiuzhen; Ma, Jinhu (Frontiers in Plant Science, 2025)
IntroductionPerilla (Perilla frutescens (L.) Britt.), a valuable source of omega-3 oils and bioactive compounds in Asia, exhibits poor seed storage and germination performance. Understanding the genetic basis of desiccation tolerance (DT) during seed development is essential for improving perilla cultivation, yet these mechanisms remain largely unknown.MethodsWe measured phenotypic and physiological parameters of perilla seeds at different developmental stages and performed transcriptome analysis to identify differentially expressed genes (DEGs). Using WGCNA, we correlated these DEGs with physiological traits to identify key modules.ResultsWe identified the D17-D27 stage as the critical window for DT acquisition in perilla seeds. Transcriptome analysis revealed 14,040 DEGs across different developmental stages. Through WGCNA analysis, we identified two key regulatory modules: the MEcoral module, which maintains membrane integrity through lipid metabolism, endoplasmic reticulum protein processing, and ABA signaling; and the MElavenderblush2 module, which regulates energy supply and cell wall remodeling via photosynthetic carbon metabolism and GA signaling. The core gene network (ABI5/BBX22/MADS3) suggests that the BBX family may serve as a crucial integrator, coordinating ABA, heat stress, and light signaling pathways to regulate antioxidant defense and energy metabolism, thereby enhancing seed adaptability.DiscussionThis study elucidates the mechanisms underlying DT acquisition in perilla seeds and provides a theoretical basis for the genetic improvement of crop stress resistance.